Sciatic Nerve Intrafascicular Injection Induces Neuropathy by Activating the Matrix Modulators MMP-9 and TIMP-1 - Tseng, Kuang-Yi; Wang, Hung-Chen; Cheng, Kai-Feng; Wang, Yi-Hsuan; Chang, Lin-Li; Cheng, Kuang-I (Frontiers in Pharmacology, 2022)
Background: Peripheral nerve block (PNB) under echo guidance may not prevent intrafascicular anesthetic injection-induced nerve injury. This study investigated whether unintended needle piercing alone, or the intrafascicular nerve injectant could induce neuropathy. Methods: 120 adult male Sprague-Dawley rats were divided into four groups: 1) group S, only the left sciatic nerve was exposed; 2) group InF-P, the left sciatic nerve was exposed and pierced with a 30 G needle; 3) group InF-S, left sciatic nerve was exposed and injected with saline (0.9% NaCl 30 µL); 4) group InF-R, left sciatic nerve was exposed and injected with 0.5% (5 mg/mL, 30 µL) ropivacaine. Behaviors of thermal and mechanical stimuli responses from hindpaws, sciatic nerve vascular permeability and tight junction protein expression, and macrophage infiltration were assessed. Pro-inflammatory cytokine expression and TIMP-1 and MMP-9 activation at the injection site and the swollen, and distal sites of the sciatic nerve were measured by cytokine array, western blotting, and immunofluorescence of POh14 and POD3. Results: Intrafascicular saline and ropivacaine into the sciatic nerve, but not needle piercing alone, significantly induced mechanical allodynia that lasted for seven days. In addition, the prior groups increased vascular permeability and macrophage infiltration, especially in the swollen site of the sciatic nerve. Thermal hypersensitivity was induced and lasted for only 3 days after intrafascicular saline injection. Obvious upregulation of TIMP-1 and MMP-9 on POh6 and POh14 occurred regardless of intrafascicular injection or needle piercing. Compared to the needle piercing group, the ratio of MMP-9/TIMP-1 was significantly higher in the intrafascicular injectant groups at the injected and swollen sites of the sciatic nerve. Although no gross changes in the expressions of tight junction proteins (TJPs) claudin-5 and ZO-1, the TJPs turned to apparent fragmentation and fenestration-like degenerative change in swollen endothelial cells and thickened microvessels. Conclusion: Intrafascicular nerve injection is a distinct mechanism that induces neuropathy. It is likely that the InF nerve injection-induced neuropathy was largely due to dramatic, but transient, increases in enzymatic activities of MMP-9 and activating TIMP-1 in the operated nerves. The changes in enzymatic activities then contributed to certain levels of extracellular matrix degradation, which leads to increases in endoneurial vascular permeability.